Anticariogenic efficacy of a saliva biomimetic in head‐and‐neck cancer patients undergoing radiotherapy. (11th November 2018) - Sim, CPC; Walker, GD; Manton, DJ; Soong, YL; Wee, JTS; Adams, GG; Reynolds, EC
Abstract: Background: The aim of this study was to investigate the effect of treatment with the saliva biomimetic, casein phosphopeptide‐amorphous calcium phosphate (CPP‐ACP) and SnF2 /NaF compared with SnF2 /NaF alone on coronal surface caries progression in head‐and‐neck cancer patients undergoing radiotherapy. Methods: Twenty‐four participants were randomized into two groups. Both groups used 0.4% SnF2 gel and a 0.32% NaF toothpaste; the test group also applied a crème containing 10% CPP‐ACP three times daily while the control group used an identical crème without CPP‐ACP (placebo). Resting saliva flow rate and saliva fluoride concentrations were determined. Caries status was assessed using ICDASII at baseline and 12‐weeks postradiotherapy. Data were statistically analysed using a linear mixed effects model. Results: Both groups showed significantly reduced resting saliva flow rate ( P < 0.001) postradiotherapy. There were no significant differences in flow rates and fluoride concentration between groups. The CPP‐ACP group exhibited a significant ( P < 0.05) 51% reduction in coronal surface caries progression compared with the placebo group. Conclusion: Resting salivary flow rate was significantly reduced in head‐and‐neck cancer patients following radiotherapy and use of CPP‐ACP with SnF2 /NaF significantly lowered caries progression compared with SnF2 /NaF alone.